2017
DOI: 10.1002/jgt.22166
|View full text |Cite
|
Sign up to set email alerts
|

Smallest graphs with given generalized quaternion automorphism group

Abstract: For n≥3, a smallest graph whose automorphism group is isomorphic to the generalized quaternion group is constructed. If n≠3, then such a graph has 2n+1 vertices and 2n+2 edges. In the special case when n=3, a smallest graph has 16 vertices but 44 edges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Suppose, conversely, that w ∼ a 2 u ⇐⇒ w ∼ a 6 u. (10) Let B = {w, a 4 w, u, a 4 u}. Define φ : V (Γ) → V (Γ) to be the map…”
Section: Proof Of Theorem 1: the Bound α(G) > |G|mentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose, conversely, that w ∼ a 2 u ⇐⇒ w ∼ a 6 u. (10) Let B = {w, a 4 w, u, a 4 u}. Define φ : V (Γ) → V (Γ) to be the map…”
Section: Proof Of Theorem 1: the Bound α(G) > |G|mentioning
confidence: 99%
“…In [4] it is shown that every finite group can be realised, up to isomorphism, as the automorphism group of a finite graph; in fact, for every finite group G there exist infinitely many finite graphs having automorphism group isomorphic to G. Given a finite group G, define α(G) to be the smallest number of vertices of any graph Γ having Aut(Γ) ∼ = G. The problem of finding α(G) has been considered by many authors. The value of α(G) has been determined in [1] for abelian groups G, in [8], [9], [11], [15] for dihedral groups G and in [10] for generalised quaternion groups G. The question has also been investigated for several families of finite simple groups in [14]. A recent survey on this problem can be found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the dataset DS 5 Among the 18 graphs, we could identify 18 graphs to be non-isomorphic with distinct sequences, which has taken only 8.4866 seconds in total, the existing isomorphism algorithm on 18 2 pairs takes 8.3194 seconds. On the dataset DS 6 Among the 167 graphs, we could identify 146 graphs to be non-isomorphic with distinct sequences, and remaining 21 graphs were classified in to 8 equivalence classes, having v = {2, 2, 2, 2, 2, 3, 3, 5}, the elements of v are in each of the class.…”
Section: Computation and Analysismentioning
confidence: 99%
“…Maximal clique and graph automorphism problems are interesting and long standing problems in graph theory. Lots research works are done on graph automorphism problem [14,15,16,17,18,19] and clique problem [20,21,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are groups which admit a graphical regular representation, for such groups µ(G) ≤ |G|. For some recent work see [6], [7], [9].…”
Section: Introductionmentioning
confidence: 99%